SOLAR ENERGY AS A SOURCE OF ELECTRIC ENERGY - Xusniddinov , Faxriddin Shamsiddinovich; Sultanxodjayeva, Gulnoza Shuxratovna (Innovative Development in Educational Activities, 2023)
The article is devoted to the current problem of using solar energy as the main source of consumer power. The author gives a generalized description of the methods of converting solar energy into other types of energy. Also, state plans for the development of solar energy in various countries of the world were considered and favorable conditions for installing solar panels in the world were considered. The article reveals the problems of non-competitiveness of solar energy in relation to a given time and how this can be dealt with.